AN ANALYSIS OF STUDENTS’ ABILITY IN USING AUXILIARY VERB OF PASSIVE VOICE SENTENCES AT THIRD SEMESTER OF STKIP YPM - Elmaida Elmaida (Universitas Mahaputra Muhammad Yamin, 2020)
This research studies about the students’ ability in using auxiliary verb on passive voice sentences at the English Department students STKIP YPM. The purpose o f this research was to find out the students’ understanding in using auxiliary verb on passive voice sentences at the third semester STKIP YPM. This research was descriptive qualitative method. The population was 15 students at third semester on English Department STKIP YPM. They were selected as the sample by using total sampling technique. The data was collected by using writing test on passive voice sentences. The finding showed that students’ understanding in using auxiliary verb on passive voices sentences at third semester of English Education Program of STKIP YPM in academic year of 2015/2016 were good enough.